2007
DOI: 10.1021/ja076802c
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective, Organocatalytic Oxy-Michael Addition to γ/δ-Hydroxy-α,β-enones:  Boronate-Amine Complexes as Chiral Hydroxide Synthons

Abstract: An organocatalytic, enantioselective oxy-Michael addition to achiral γ-and δ-hydroxy-α,β-enones was developed. The key transformation is an unprecedented, asymmetric conjugate addition triggered by complexation between an in situ generated boronic acid hemiester and a chiral amine catalyst. Functionally, the intermediate amine-boronate complex acts as a chiral hydroxide surrogate or synthon. The resultant chiral β-hydroxy-ketones are obtained in good to excellent yields and high ee following mild oxidative rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(56 citation statements)
references
References 22 publications
(21 reference statements)
1
55
0
Order By: Relevance
“…[7] Other organocatalytic approaches have also been successful, including the secondary amine-catalysed addition of benzaldoxime to a,b-unsaturated aldehydes developed by Jørgensen; [8] and the bifunctional Brønsted acid-base catalytic intramolecular oxy-Michael reactions for boronic hemiesters developed by Falck. [9] Organocatalysed intramolecular oxy-Michael reactions have also been reported by Scheidt [10] and separately by Hintermann [11] in the enantioselective syntheses of flavanones. Many of these reactions have been found to be of use in the synthesis of natural products.…”
Section: Introductionmentioning
confidence: 82%
“…[7] Other organocatalytic approaches have also been successful, including the secondary amine-catalysed addition of benzaldoxime to a,b-unsaturated aldehydes developed by Jørgensen; [8] and the bifunctional Brønsted acid-base catalytic intramolecular oxy-Michael reactions for boronic hemiesters developed by Falck. [9] Organocatalysed intramolecular oxy-Michael reactions have also been reported by Scheidt [10] and separately by Hintermann [11] in the enantioselective syntheses of flavanones. Many of these reactions have been found to be of use in the synthesis of natural products.…”
Section: Introductionmentioning
confidence: 82%
“…Apart from the catalysts, the nature of the acidic additive and the reagent concentration were the crucial factors for obtaining a highly efficient and general catalytic system, so their slight difference is the additive of the aromatic acid and temperature. Both gave excellent results with the corresponding phosphine derivatives (91) in high yields and enantioselectivities under optimized conditions (Scheme 29). To shed more light on the origin of the enantioselectivity, Córdova et al performed density functional theory (DFT) calculations on the P À C bond-forming step.…”
Section: Hetero-michael Reactionmentioning
confidence: 99%
“…In fact, literature examples are exclusively limited to the use of functionalized phenols as nucleophiles [91] and also a couple of elegant procedures have been reported by Jørgensen and co-workers [92] for the b-hydroxylation of a,b-unsaturated aldehydes using oximes as O-nucleophiles.…”
Section: The Construction Of Five-membered Ringsmentioning
confidence: 99%
“…64 The essential role of the aryl BA for high enantioselectivity was underlined by the formation of racemic product in its absence. However, it was observed that enantioselectivity was highly dependent on the structure of the aryl BA employed.…”
Section: Introductionmentioning
confidence: 99%